Diamond Tool Wear Measurement by Profilometry Method for Ultra-precision Machining of Silicon. (2019) - Singh, Garima; Mishra, Vinod; Karar, Vinod; Banwait, S.S
Abstract: Ultra-precision machining is used to generate the high quality surfaces in terms of nano-metric surface finish and sub-micron profile accuracy for various engineering applications. Due to unique properties of diamond i.e. high hardness, good heat conductivity and low friction co-efficient it is most suitable tool material for ultra-precision machining. Advancements in material science and growing needs for modern applications leads to development of new materials. Silicon is one of the prominent materials used for various optical applications. However processing of silicon by machining is quite difficult due to its hard and brittle nature. Diamond tool wear is one of the major issues for ultra-precision machining which leads to increase the process cost significantly. Control of tool wear mainly depends on machining parameter selection and understanding of tool wear mechanism. Wear measurement of diamond tool is essential to understand the wear mechanism, process behavior and tool life quantification. Wear measurement of nano-metric cutting edge is one of the challenging tasks. In current study machining experiments are performed on Silicon. Tool cutting edge is analyzed by profilometric measurements at different orientations. Wear of cutting edge, rake face and flank face is measured. Measurement results are very helpful for understanding the possible reasons of wear and hence to optimize the machining conditions to minimize the tool wear.